ANALISIS KEBIASAAN SARAPAN PADA CAPAIAN PRESTASI AKADEMIK SISWA DI SDN KERAS KECAMATAN SURO MAKMUR KABUPATEN ACEH SINGKIL - Berutu, Nurfiade Br; Usman, Khairul; Simanjuntak, Sorta; Winara, Dr.; Siregar, Waliyul Maulana (Jurnal Merah Putih Sekolah Dasar, 2024)
This study was conducted with the aim of describing breakfast habits on academic achievement of SDN Keras students. This research is descriptive qualitative. This research was conducted at UPTD SPF SDN Keras. The subjects consisted of 99 students and 67 parents. Data were collected through questionnaires and interviews. To check the validity of data using triangulation techniques. Data analysis techniques are done by reducing data, presenting data and drawing conclusions. The results of this study indicate that by implementing good breakfast habits, it will have an impact on improving student achievement. Keywords: Breakfast Habits, Achievements